THE FUNDAMENTALS OF TEACHING CREATIVITY (BASED ON THE EXAMPLE OF GREAT BRITAIN) - Svetlana V. Skvortsova (Russian State Vocational Pedagogical University, 2015)
The aim of the investigation is to find out the fundamentals of creative activity of pupils in a comprehensive school and reveal its main characteristics on the basis of analysis of the British system of education experience considering the original modern official educational documents devoted to optimization of education and its increased focus on the creative development of children and teenagers. Methods. Author uses the methods of theoretical analysis of original foreign materials; systematization and classification of the data from original foreign sources. Results. The main characteristics of creativity are purposefulness, aiming at search of a new idea or creation of worthy product, and also dependence on the environment that means search of sphere of educational activity for disclosing of individual creative potential of the pupil. Character of creative activity depends on personal characteristics of the performer, the high level of motivation and active use of imagination. Scientific novelty. The main characteristics of creative activity as seen by British educators are specified, particularly such feature as dependence on the environment is exposed, and the importance of using traditional teaching methods within the innovative ones is proved; the methods of teaching creativity used by British teachers are picked out and classified according to the levels of creative activity; practical recommendations for successful implementation of teaching creativity are described, such as taking advantage of spontaneous educational situations and the following changes in the work agenda. Practical significance. Analysis and systematization of the foreign researchers' experience enriches Russian theory of education with understanding the fundamentals of teaching creativity. The singled out peculiarities of teaching creativity give perspectives for the scientific substantiation of adaption of the innovative components into Russian system of education and make it possible to predict the ways of developing the process of teaching creativity in Russia. The classification of creative teaching methods and practical recommendation for their implementation can be adapted to Russian system of education.